Plasma technology for surface modification of 3D printed medical devices (Transactions on Additive Manufacturing Meets Medicine, 2024)
Additive manufacturing has become a versatile tool in medical engineering over the last decade. For medical applications the interaction of the device surface and the surrounding medium is crucial. Depending on the application adhesive or anti-adhesive properties can be necessary.Cell adhesion to implants is determined by surface chemistry and topography. These can be tailored by plasma-based processes. This allows surface modification from the gas phase, even on complex geometries. In this paper, we would like to give an overview on the advances of different plasma-based treating technologies for medical applications. Focusing on cold plasma at atmospheric pressure, the combination of treatment and 3D-printing is demonstrated. We will present the current state of the art of different plasma sources to be integrated in fused deposition modelling (FDM). Main goals of plasma treatment of polymers deposited by FDM, are the improvement of the wetting behavior, cell adhesion and the adhesion of different materials combined in the printing process.
Keywords: atmospheric pressure plasma; Additive Manufacturig; surface modification